2015
DOI: 10.1038/mt.2014.204
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Stem Cells Loaded With Hyaluronidase-expressing Oncolytic Virus for Brain Tumor Therapy

Abstract: Despite the proven safety of oncolytic viruses (OV) in clinical trials for glioblastoma (GBM), their efficacy has been hindered by suboptimal spreading within the tumor. We show that hyaluronan or hyaluronic acid (HA), an important component of extracellular matrix (ECM), is highly expressed in a majority of tumor xenografts established from patient-derived GBM lines that present both invasive and nodular phenotypes. Intratumoral injection of a conditionally replicating adenovirus expressing soluble hyaluronid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 50 publications
0
96
0
3
Order By: Relevance
“…Extracellular matrix (ECM) within GBM can hamper intratumoral spread of oncolytic viruses by presenting physical barriers . We recently demonstrated that an important component of ECM, hyaluronan, is abundant in GBM and an oncolytic virus expressing hyaluronidase mediates increased intratumoral spread and anti‐GBM potency . Simultaneous expression of TRAIL and hyaluronidase in the context of oHSV might overcome both resistance and delivery problems associated with oHSV therapy of highly invasive GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular matrix (ECM) within GBM can hamper intratumoral spread of oncolytic viruses by presenting physical barriers . We recently demonstrated that an important component of ECM, hyaluronan, is abundant in GBM and an oncolytic virus expressing hyaluronidase mediates increased intratumoral spread and anti‐GBM potency . Simultaneous expression of TRAIL and hyaluronidase in the context of oHSV might overcome both resistance and delivery problems associated with oHSV therapy of highly invasive GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Such an aggregation causes the nanoparticles to behave like larger particles [58] and may affect systemic delivery for therapeutic application in the brain. However, evaluation of potential therapeutics through direct intratumoral injection including nanoparticle delivery to in vivo models of GBM [59, 60] or at the point of patient tumor resection or biopsy [6165] in several studies indicates that such systemic transport challenges can be circumvented to facilitate therapeutic delivery in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Ein weiterer tumortherapeutischer Ansatz ist die genetische Modifikation von MSCs mit dem Genom für onkolytische Viren [31][32][33]. Solche Viren sind von Natur aus oder durch genetische Modifikation in der Lage, bevorzugt Tumorzellen zu infizieren bzw.…”
Section: Genetisch Modifizierte Mesenchymale Stromazellen (Mscs)unclassified